High birth weight in a suburban hospital in Cameroon: an analysis of the clinical cut-off, prevalence, predictors and adverse outcomes. Issue 6 (29th June 2016) - Choukem, Simeon-Pierre; Njim, Tsi; Atashili, Julius; Hamilton-Shield, Julian P; Mbu, Robinson
Abstract : Background and aims: High birth weight (HBW) increases the risk of maternal and fetal morbidity and mortality. Its prevalence and adverse outcomes may be reduced if risk factors are identified and managed during pregnancy. The cut-off value for HBW remains debatable. The objectives of this study were to identify the optimal cut-off value and determine the prevalence, predictors and adverse outcomes of HBW in a suburban area of Cameroon. Design: A 6-year retrospective register analysis and a 3-month prospective phase. Setting: A secondary care level (regional) hospital in the city of Buea (southwest region of Cameroon). Participants: Women who delivered in this hospital over a 6-year period (retrospective phase) and consenting pregnant mothers and their infants (singletons, born at >28 weeks gestation) (prospective phase). Outcome measures: 90th centile of birth weights; prevalence of HBW defined as birth weight above the 90th centile; sociodemographic, maternal and obstetrical factors associated with HBW; maternal and neonatal adverse outcomes of HBW. Results: Of the 4941 newborns reviewed in registers, the 90th centile of birth weights was 3850 g. Using this new cut-off, we obtained a prevalence of 14.0% for HBW in the 200 newborns included in the prospective phase. This was significantly higher than the prevalence (9.5%) yielded when the traditional cut-off of 4000 g was used (p=0.003). None of the factors assessed was independently associated with HBW. Newborns with HBW were more likely to have shoulder dystocia (p<0.01), and their mothers more likely to suffer from prolonged labour (p=0.01) and postpartum haemorrhage (p<0.01). Conclusions: The results of this study suggest that the cut-off for HBW in this population should be 3850 g. Thus, 3 of every 10 babies born with HBW in this hospital are likely not receiving optimal postnatal care because 4000 g is currently used to qualify for additional support.